Effective Stakeholder Engagement in Coastal Rransitions: Floating away from the DAD Approach towards the MOM Method - Kelly, Miriah; Axon, Stephen (Blue Economy: People and Regions in Transitions, 2022)
Emerging literature on coastal transitions in the face of the climate crisis establishes a need for identifying appropriate stakeholder engagement processes for
Num Pages: 12
Keywords: dept.egm